ANALISIS PENGANGGURAN TERBUKA DI PROVINSI BENGKULU TAHUN 2015-2024 - Dina Kristina Margaretta Pandiangan; Rapides Okta Fanisha Pandiangan; Sri Ningsih (Jurnal Riset Multidisiplin Edukasi, 2026)
Open unemployment is a macroeconomic issue that directly impacts public welfare and poverty levels. This study analyzes the trend of open unemployment in Bengkulu Province for the period 2015–2024 using data from the Central Statistics Agency. The analysis shows that the open unemployment rate in Bengkulu tends to be lower than the national average, with a consistent downward trend except for a spike in 2020 due to the COVID-19 pandemic. Local sectors such as agriculture and plantations have proven more resilient to crises than the service sector in urban areas. Post-pandemic economic recovery is reflected in a decrease in the Open Unemployment Rate (TPT) to 3.11% in 2024. This study emphasizes the importance of strengthening the local economic sector, diversifying employment through MSMEs and the creative sector, and training workforce skills as strategies to reduce unemployment and improve public welfare.